(untitled) (Eurasian Medical Research Periodical, 2023)
Community-acquired pneumonia and acute obstructive bronchitis occupy the largest proportion among respiratory diseases in children undergoing inpatient treatment. Currently, there is an increase in the number of obstructive bronchitis, which is 4.5-7.5 thousand cases per 100 thousand children. It is believed that this disease is the leader in the number of requests for outpatient medical care, while in 25-30% of young children respiratory infections occur with a clinic of obstructive bronchitis of varying severity, and in 30-50% of these cases the disease can take a protracted, undulating or recurrent course. In the course of a comparative analysis of the dynamics of clinical symptoms of acute obstructive bronchitis in patients of groups I and II, several significant distinguishing symptoms were identified in the group of children with bronchial obstructive syndrome. These features can help in earlier diagnosis and determination of the characteristics of the treatment of the disease in this group of patients